2022
DOI: 10.1093/trstmh/trac089
|View full text |Cite
|
Sign up to set email alerts
|

Multicountry study of SARS-CoV-2 and associated risk factors among healthcare workers in Côte d'Ivoire, Burkina Faso and South Africa

Abstract: Background Reports on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spread across Africa have varied, including among healthcare workers (HCWs). This study assessed the comparative SARS-CoV-2 burden and associated risk factors among HCWs in three African countries. Methods A multicentre study was conducted at regional healthcare facilities in Côte d’Ivoire (CIV), Burkina Faso (BF) and South Africa (SA) from Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This indicate that there was an increased risk of SARS-CoV-2 exposure among allied HCWS compared medical doctors and nursing cadres. Results are concordant with one previous observational study, which had shown increasing odds off seropositivity in allied health professionals compared to medical doctors (32). The reasons behind this finding are necessary to be explored in order to protect these allied HCWs from the risk of acquiring communicable diseases in their work setting…”
Section: Discussionsupporting
confidence: 90%
“…This indicate that there was an increased risk of SARS-CoV-2 exposure among allied HCWS compared medical doctors and nursing cadres. Results are concordant with one previous observational study, which had shown increasing odds off seropositivity in allied health professionals compared to medical doctors (32). The reasons behind this finding are necessary to be explored in order to protect these allied HCWs from the risk of acquiring communicable diseases in their work setting…”
Section: Discussionsupporting
confidence: 90%
“…However, these results were not replicated in participants from Natitingou. Similarly, other studies also failed to find an association between SARS-CoV-2 seropositivity and presence of comorbidities [ 36 39 ]. In this sense, there are still gaps in the understanding of antibody levels and duration of protection against SARS-CoV-2 in people with comorbidities.…”
Section: Discussionmentioning
confidence: 97%
“…However, there is emerging evidence that transmission in SSA has been at least as high or even higher than in other continents [9], although these data should be interpreted with caution as some studies have important limitations. Most of them do not represent the entire population, rather specific groups, generally high risk groups [10]. In addition, SARS-CoV-2 prevalence may be overestimated as SARS-CoV-2 antibodies may cross-react with other viral or parasitic antibodies in the region, such as IgG antibodies against the spike and nucleocapsid proteins of different human coronaviruses: HCoV-OC43, HKU-1, NL63 and 229E, as well as SARS and MERS [11], and IgG directed against Plasmodium falciparum antigens where malaria is endemic [12].…”
Section: Introductionmentioning
confidence: 99%